Pemanfaatan Mikroba Tanah dalam Pembuatan Pupuk Organik serta Peranannya terhadap Tanah Aluvial dan Pertumbuhan Bibit Tanaman Kakao - Agustinus Mangungsong; Soemarsono; Fatardho Zudri (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
The use of microorganisms and organic materials in agriculture because it can increase the availability of soil nutrients and absorption by plants and form soil structures becomes looser. The purpose of this study was to obtain the most effective types of decomposer microorganisms and the most appropriate organic fertilizer (compost) to improve the physical, chemical and biological properties of alluvial soils and their role in plants in cocoa seedlings. The research was conducted in the Laboratory of Soil, Greenhouses and experimental gardens of the Agricultural Polytechnic State Payakumbuh Tanjung Pati Kabupaten Lima Puluh Kota. The study uses experimental methods. The study used a factorial randomized block design on soil tests and a complete randomized design for the cacao seedling test. Parameters observed were alluvial soil pH, N-total alluvial soil, P-available alluvial soil, K-exchangeable alluvial soil, alluvial soil volume weight, the total population of alluvial soil bacteria, plant height of cocoa seedlings, number of leaves of cocoa seedlings, stem diameter of cocoa seedlings, dry weight of cacao seed stover. The results of the study there were no differences in the treatment of the type of compost and the type of microorganisms to the pH value of the soil. Types of microorganisms with the type of compost can increase the total N content in alluvial soil. The use of compost types and types of microorganisms had a significantly different effect on the value of soil volume weight, P-available, K-exchangeable, and the total population of alluvial soil bacteria. Treatment of Type of Compost Tithonia and Types of Pseudomonas fluorescens + Trichoderma harzianum microorganisms have the best influence on soil test variables. The application of cacao seedlings at the dose of Tithonia compost 1.25 kg/polybag provides the best growth. Keywords: Alluvial soil, cocoa seedlings, compost, microorganisms